A study on the amounts of plant nutrients and organic matter carried into Lake Hazar (Elazig-Turkey) - Sen, B; Alp, MT; Özrenk, F; Ercan, Y; Yildirim, V (Inst Lebensmitteltechnologie Analytische Chemie, 1999)
Lake Hazar is one of the largest lakes in Eastern Anatolia extensively used for recreational purposes and also for fishing. Kurk and Zikkim streams are the two most important inflows into the lake. It is a well known fact that inflows induce the eutrophication and pollution in a lake. Therefore, it is necessary to determine eutrophication and pollution loads of running waters entering the lakes. For this purpose, loads of plant nutrients and organic matter carried by Kurk and Zikkim streams into the lake were monitored for a period of one year.
Keywords: nutrient loading; organic matter; stream; Lake Hazer; Turkey